Insights into the expression of DNA (de)methylation genes responsive to nitric oxide signaling in potato resistance to late blight disease - Drozda, Andżelika; Kurpisz, Barbara; Guan, Yufeng; Arasimowicz-Jelonek, Magdalena; Plich, Jarosław; Jagodzik, Przemysław; Kuźnicki, Daniel; Floryszak-Wieczorek, Jolanta (Frontiers in Plant Science, 2022)
Our previous study concerning the pathogen-induced biphasic pattern of nitric oxide (NO) burst revealed that the decline phase and a low level of NO, due to S-nitrosoglutathione reductase (GSNOR) activity, might be decisive in the upregulation of stress-sensitive genes via histone H3/H4 methylation in potato leaves inoculated with avr P. infestans. The present study refers to the NO-related impact on genes regulating DNA (de)methylation, being in dialog with histone methylation. The excessive amounts of NO after the pathogen or GSNO treatment forced the transient upregulation of histone SUVH4 methylation and DNA hypermethylation. Then the diminished NO bioavailability reduced the SUVH4-mediated suppressive H3K9me2 mark on the R3a gene promoter and enhanced its transcription. However, we found that the R3a gene is likely to be controlled by the RdDM methylation pathway. The data revealed the time-dependent downregulation of the DCL3, AGO4, and miR482e genes, exerting upregulation of the targeted R3a gene correlated with ROS1 overexpression. Based on these results, we postulate that the biphasic waves of NO burst in response to the pathogen appear crucial in establishing potato resistance to late blight through the RdDM pathway controlling R gene expression.